Safety and Efficacy of Hepatitis B Vaccination in Cirrhosis of Liver - D. Ajith Roni; Rama Mohan Pathapati; A. Sathish Kumar; Lalit Nihal; K. Sridhar; Sujith Tumkur Rajashekar (Advances in Virology)
Introduction. Patients with chronic liver disease (CLD) are more likely to have severe morbidity and fatality rate due to superimposed acute or chronic hepatitis B (HBV) infection. The literature has shown that hepatitis B vaccines are safe and effective in patients with CLD, but the data in cirrhosis liver is lacking. We assessed the safety and immunogenicity of HBV vaccine in patients with cirrhosis liver. Methods. CTP classes A and B CLD patients negative for hepatitis B surface antigen and antibody to hepatitis B core antigen were included. All patients received three doses of hepatitis B vaccine 20 mcg intramuscularly at 0, 30, and 60 days. Anti-HBs antibody was measured after 120 days. Results. 52 patients with mean age years were studied. Response rates in CTP classes A and B were 88% and 33.3%. We observed that the alcoholic chronic liver disease had less antibody response (44%) than other causes of chronic liver disease such as cryptogenic 69% and HCV 75%. Conclusions. Patients with cirrhosis liver will have low antibody hepatitis B titers compared to general population. As the age and liver disease progress, the response rate for hepatitis B vaccination will still remain to be weaker.